Cannabinoids and alcohol co-exposure modulate pathogen-induced pulmonary immune responses - Parker, De’Jana; Sivaraman, Vijay (Frontiers in Immunology, 2025)
Both alcohol and cannabinoid misuse cause substantial societal problems individually, and cannabis is the most popular illicit drug used simultaneously with alcohol. The role of endocannabinoids (eCB) and cognate receptors in the regulation of inflammation is clinically relevant; however, the role of cannabinoid receptors (CBRs) specifically in pulmonary inflammation and associated lung pathobiology remains elusive. For this study, we investigated the effects of binge cannabinoid exposure on pathogen-induced pulmonary inflammation. We also describe a binge ethanol + cannabinoid adolescent mouse model of pathogen-induced pulmonary inflammation by Klebsiella pneumoniae (K. pneumoniae) infection. We show that adolescent cannabinoid exposure primes the lung to a more severe inflammation in adulthood, and this response is mitigated by cannabinoid antagonists. We also show that ethanol and cannabinoid pre-exposure followed by microbial challenge yielded CBR-dependent pulmonary immune activation via danger-associated molecular pattern (DAMP) release. This research may shed light on CB signaling as it relates to DAMPs and can provide a framework to develop potential novel therapeutics in polysubstance use disorders.